The Vicious Circle of Financial Exclusion: An Empirical Study in West Bengal - Mazumder, Rabin (Indian Journal of Finance, 2013)
Despite many efforts in the last twenty years, access to finance has remained scarce in rural India. Inadequate access to financial services is considered one of the main reasons behind inadequate economic opportunity and abject poverty in the developing countries. The present study is a research conducted among rural households in Howrah and Murshidabad districts of West Bengal. The main aim of this paper is to explore the various factors behind financial exclusion in West Bengal. The principal sources for financial exclusion are generated from the demand side and supply side factors. The study is essentially based on primary data captured through a structured questionnaire and was administered to a total of 150 respondents. In order to find out the causes behind the financial exclusion inside the demand and supply related factors, binary logistic regression method was considered to be appropriate. The results of the analysis suggess that from the demand side, income of the households, awareness, and education have a significant role on financial exclusion. From the supply side, cumbersome documentation process has a marginal effect on it. Thus, appropriate policies are required to solve these problems.